Revolutionizing healthcare through artificial intelligence / Assoc. Prof. Dr Fazlin Mohd Fauzi - Mohd Fauzi, Fazlin (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The healthcare industry is continuously evolving, with new advancements and technologies emerging frequently. One of the most promising developments in recent years is the increasing integration of artificial intelligence (AI) in healthcare. AI has the potential to revolutionize healthcare by predicting and preventing disease outbreaks, as well as identifying the most effective treatments for individual patients. With the ability to analyze vast amounts of data, AI algorithms can uncover patterns and relationships that may not be immediately apparent to humans.